Des femmes dans la cité : les sages-femmes péruviennes du XIXe siècle - Lissell Quiroz-Pérez (Nuevo mundo - Mundos Nuevos, 2014)
This paper seeks to show how the changing paradigm of birth, which occurred at the end of the eighteenth century, contributed to the appearance and development of a new profession, that of the professional midwife. The birth of this profession occurred in a state-building context. Haunted by the fear of depopulation, the Peruvian Enlightenment elite put an end to the practices of traditional birth attendants and provided better support to women in childbirth. In 1826, a Maternité in the Parisian model was created; it combined a birth clinic and a school of midwifery. The professional midwifes, who worked with upper class women as well as in the remote areas of the country acquired a special status which widened and sometimes questioned the traditional female sphere of action. They were the first women to make their entrance in the university, to work in hospitals and as independent midwives, and to testify in criminal courts. Although they were not organized in corporations, skilled Peruvian midwives gradually managed to step into the public sphere through unexpected venues which increased their agency.